DEVELOPMENT OF MEDICAL LITERACY OF STUDENTS BY TEACHING THE MEDICINAL PROPERTIES OF MEDICINAL PLANTS GROWING IN UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In the article, the forests of Uzbekistan are distinguished by the richness of a variety of medicinal trees, shrubs and herbs. Human life is inextricably linked with the plant world. Plants were widely used not only as food, but also as a source of biologically active substances. There is evidence that medicinal plants were used for medicinal purposes as early as 5,000 years ago. Medicinal plants have served as the only source of medicines for long historical periods.